Effects of an exopolysaccharide from Lactococcus lactis Z-2 on innate immune response, antioxidant activity, and disease resistance against Aeromonas hydrophila in Cyprinus carpio L. Issue 98 (March 2020) - Feng, Junchang; Cai, Zhongliang; Chen, Yongyan; Zhu, Haoyong; Chang, Xulu; Wang, Xianfeng; Liu, Zhen; Zhang, Jianxin; Nie, Guoxing
Abstract: Microbial exopolysaccharides (EPS) from Lactococcus have been found to have an important role in the probiotic activity of this bacterium; however, the immunomodulatory and antioxidant activities have not been fully explored in aquaculture. In the present study, we investigated EPS-2 from Lactococcus lactis Z-2, isolated from healthy common carp, for its immunomodulatory and antioxidant effects and disease resistance against Aeromonas hydrophila in Cyprinus carpio L. We found that the molecular weight of EPS-2 was 18.65 KDa. The monosaccharide composition of this polymer was rhamnose, xylose, mannose, glucose, and galactose at a molar percentage of 13.3%, 14.1%, 18.5%, 27.4%, and 26.7%, respectively. EPS-2 treatment could modulate the immune responses in vitro and in vivo . In vitro tests showed that EPS-2 could significantly enhance the proliferation and phagocytosis activities ( P  < 0.05) as well as induce the production of nitic oxide (NO), pro-inflammatory cytokines (TNF-α, IL-1β, IL-6), and anti-inflammatory cytokines (IL-10, TGF-β) ( P  < 0.05) in head kidney cells. When the fish were gavaged with three different concentrations of EPS-2 (250, 500, 1000 μg/mL) for 7 days and infected with A. hydrophila, different expression patterns of the NO, cytokines, lysozyme (LZM), and alkaline phosphatase (AKP) in the serum and of antioxidants (T-AOC, SOD, CAT, GSH, GSH-Px and MDA) in hepatopancreas were observed. Before infection with A. hydrophila, EPS-2 supplementation significantly up-regulated the NO production, protein levels of pro-inflammatory cytokines (TNF-α, IL-1β, IL-6), LZM and AKP activities, and levels of antioxidant molecules compared to those in the negative (G1) group ( P  < 0.05), whereas levels of NO and pro-inflammatory cytokines and LZM and AKP activities were significantly lower than those in the positive (G2) group after infection ( P  < 0.05). However, whether infected or not, the expression levels of anti-inflammatory cytokines (IL-10, TGF-β) were significantly increased in the EPS-2 treatment groups ( P  < 0.05). These results indicate that EPS-2 has immunomodulatory and antioxidant effects on common carp, both in vitro and/or in vivo, and can be applied as a common carp feed supplement to enhance fish immunity and disease resistance against A. hydrophila . Highlights: A water soluble exopolysaccharide (EPS-2) was prepared from Lactococcus lactis Z-2. EPS-2 can improve the head kidney cells' proliferation and phagocytosis. EPS-2 can induce the secretion of cytokines and NO in vitro and in vivo. EPS-2 can enhance the antioxidant substances and the LZM, AKP activities in common carp. EPS-2 can enhance disease resistance against A. hydrophila in common carp.